Girl archaeologist : sisterhood in a sexist profession - Kehoe, Alice Beck (University of Nebraska Press, 2022)
"Girl Archaeologist illuminates the life and trailblazing career of Alice Kehoe, a woman with a family who was always, also, an archaeologist"--
Keywords: Kehoe, Alice Beck, : 1934-; seksismi; antropologia; arkeologit; naiset; naisen asema; intiaanit; Sexism in anthropology; Women archaeologists : United States : Biography; Archaeologists : United States : Biography; Indians of North America : Great Plains; Women archaeologists; Sexism; Femmes archéologues : États-Unis : Biographies; Archéologues : États-Unis : Biographies; Indiens d'Amérique : Grandes Plaines; Kvinnliga arkeologer; SOCIAL SCIENCE / Archaeology; BIOGRAPHY & AUTOBIOGRAPHY / Women; Archaeologists; Indians of North America; Women archaeologists; Yhdysvallat; Förenta staterna; Great Plains; United States; Suuret tasangot